2020
DOI: 10.1111/aos.14688
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of refractive prediction for intraoperative aberrometry and Barrett True K no history formula in cataract surgery patients with prior radial keratotomy

Abstract: Purpose To compare prediction errors of the Barrett True K No History (Barrett TKNH) formula and intraoperative aberrometry (IA) in eyes with prior radial keratotomy (RK). Methods A retrospective, non‐randomized study of all patients with RK who underwent cataract surgery using IA at the UCHealth Sue Anschutz‐Rodgers Eye Center from 2014 to 2019 was conducted. Refraction prediction error (RPE) for IA and Barrett TKNH was compared. General linear modelling accounting for the correlation between eyes was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…These findings corroborate the findings of previously published studies. 8,15,21 To determine if prediction accuracy of the two methods is affected by AL, the correlation between absolute PE and AL was assessed. While there are studies that evaluate the effect of AL on the prediction accuracy of IOL formulas in eyes without previous LVC and in post-myopic LVC eyes, 23 to the best of our knowledge, this is the first study to also stratify the results by AL in post-hyperopic LVC and post-RK eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate the findings of previously published studies. 8,15,21 To determine if prediction accuracy of the two methods is affected by AL, the correlation between absolute PE and AL was assessed. While there are studies that evaluate the effect of AL on the prediction accuracy of IOL formulas in eyes without previous LVC and in post-myopic LVC eyes, 23 to the best of our knowledge, this is the first study to also stratify the results by AL in post-hyperopic LVC and post-RK eyes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies have reported on the superiority of the Barrett formulas (Barrett Universal II and Barrett True-K) compared to other preoperative calculation methods in predicting IOL power in eyes with or without previous refractive surgery. [13][14][15][16] Intraoperative aberrometry (IA) was designed to increase the accuracy of IOL power calculation and to reduce residual refractive error after cataract surgery. The ORA System with VerifEye+ (Alcon Surgical Inc.) can calculate IOL power based on aphakic spherical equivalent, preoperative axial length (AL) and corneal power.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative aberrometry appears to be more accurate in radial keratotomy eyes with less than eight cuts than in eyes with eight or more cuts, based on a series by Dawson et al [43]. They found that intraoperative aberrometry had a mean absolute error of 0.30D in eyes with less than eight cuts and 0.80D in eyes with eight or more cuts ( P = 0.0001), and for preoperative calculations with the Barrett True-K No History formula a mean absolute error of 0.35D in eyes with less than eight cuts and 0.74D in eyes with eight or more cuts ( P = 0.008) [43].…”
Section: Intraoperative Aberrometry In Eyes With History Of Refractiv...mentioning
confidence: 99%
“…& ]. In contrast, there are numerous studies that instead focus on either routine/typical non-post-refractive surgery cases alone [6,9,10 ,11, 14,30-32,33 & ,34-38] or on subsets of atypical patients [29,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]. This trend in publications may be at least in part a reflection that in the real world, many cataract surgeons utilize intraoperative aberrometry selectively rather than broadly.…”
Section: Andand 28mentioning
confidence: 99%
“…Similarly, use of intraoperative aberrometry was not explored in this study and would be of interest, although its use in eyes with isolated RK or LASIK/PRK has been equivocal to using the Barrett True-K formula. 7,8 In addition, we did not have access to the refractive surgery records, and it may be important to explore the characteristics of the previous LASIK/PRK enhancements (hyperopic or myopic correction).…”
mentioning
confidence: 99%